2021
DOI: 10.1002/stc.2773
|View full text |Cite
|
Sign up to set email alerts
|

Bridge scour characteristic curve for natural frequency‐based bridge scour monitoring using simulation‐based optimization

Abstract: Summary This study addresses a key issue that prevents the wide application of the novel predominant natural frequency (PNF)‐based method for bridge scour monitoring, which is also applicable to the frequency‐based health monitoring of other structures with soil–structure interaction. This issue is that no theory or method is currently available to guide the prediction of scour depths based on measured PNFs. The most feasible way is to first measure a few scour depths and their corresponding PNFs for obtaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Through theoretical, numerical and laboratory test studies, it is proven that for piers partially embedded in the soil, using the Winkler model to simulate soil-structure interaction can more accurately predict pier frequency than the Pasternak model [93]. Further, a BSCC prediction method based on the Winkler model and global optimization technology was proposed and was verified via numerical simulation [94]. The results showed that accurate BSCC can be obtained using only a small number of samples (2~4) within a small scour depth (0.2~0.5 m).…”
Section: Scour Depth Identification For Middle-small Span Bridgesmentioning
confidence: 97%
See 1 more Smart Citation
“…Through theoretical, numerical and laboratory test studies, it is proven that for piers partially embedded in the soil, using the Winkler model to simulate soil-structure interaction can more accurately predict pier frequency than the Pasternak model [93]. Further, a BSCC prediction method based on the Winkler model and global optimization technology was proposed and was verified via numerical simulation [94]. The results showed that accurate BSCC can be obtained using only a small number of samples (2~4) within a small scour depth (0.2~0.5 m).…”
Section: Scour Depth Identification For Middle-small Span Bridgesmentioning
confidence: 97%
“…Bao et al [93,94] proposed using the bridge scour characteristic curve (BSCC) to predict the scour depth of pile foundation. BSCC represents the relationship between pier frequency and scour depth.…”
Section: Scour Depth Identification For Middle-small Span Bridgesmentioning
confidence: 99%
“…Similarly, Prendergast et al [20] investigates the local sensitivity to scour of the vibration modes of a bridge, using a vehicle-bridge-soil dynamic interaction model for identifying both the occurrence and the location of the scour. Bao and Liu [21] developed a formula for predicting the predominant natural frequency of bridge piers under future higher scour widths by measuring only the response under a few small scour widths. Other recent numerical and experimental studies have been carried out on the use of ambient vibration recordings for scour identification [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%